Понятійне поле української народної молитви: історіографічний аспект - Гунчик, Ігор (Slavia Orientalis, 2026)
The article attempts to outline in a diachronic perspective the boundaries of the use and semantic content of the term ‘folk prayer’ and related concepts. Having analysed the most important works of researchers on this issue and relevant folklore and ethnographic material from different regions of Ukraine for the period from the nineteenth – to the early twenty‑first century, the author argues that it was used not only in the academic field but also in the folk terminological tradition to denote folklore texts that are correlated with incantations, spells, sayings, curses and other typologically related entities. It is noted that in modern Ukrainian academic discourse, folk prayer is considered as a separate original ethno‑cultural phenomenon that belongs to magical and sacred folklore and has a Christianized religious basis. The author points out the pan‑Slavic context of the spread of folk prayer as an ancient ethno‑cultural phenomenon, the existence of which is characteristic of national Polish and Czech oral traditions, ones still insufficiently studied.